Always On and Always With Mobile Tablet Devices: A Qualitative Study on How Young Adults Negotiate With Continuous Connected Presence. (October 2013) - Park, Sora
Internet-enabled mobile devices expand the virtual spaces of Internet users. Mobile Internet users encounter continuous connectivity where they are not only always on but also always with the device. Users are presented with situations of continuous connected presence requiring them to deal with the overwhelming volume of virtual interaction. This study reports from a longitudinal study of 35 university students in Australia conducted in 2011/2012. Mobile tablet devices were given to participants who had never owned one before, to be observed over a period of 1 year. By qualitatively exploring how users experience and negotiate with the added virtual space, this study found that while users benefit from continuous connectivity, they also adopt strategies to disconnect from the ubiquitous access especially when engaging in tasks that require undivided attention. New users go through adjustment by developing their own involvement shield strategies while experimenting with online colocation and copresence.